Method for directionally preparing multi-scale micro-nano fiber modified polymer aggregates
Through the method of liquid hydrophobic-coupling of double-coated micro-nanofibers, the problem of uneven dispersion and agglomeration of micro-nanofibers in polymer matrix is solved, and the high strength and dimensional stability of composite materials are achieved, which is suitable for automobiles and electronics. Products and construction substrates and other fields.
Patent Information
- Application Number
- CN202411038696.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-07-31
AI Technical Summary
Micro-nanofibers are unevenly dispersed and easily agglomerated in polymer matrix, resulting in poor interfacial bonding and poor strength and dimensional stability of composite materials. Existing methods such as chemical modification methods or the use of coupling agents have high costs and The issue of environmental pollution.
The method of liquid hydrophobic-coupling double-coated micro-nanofibers is used to modify the micro-nanofibers to improve their compatibility and interface bonding with plastic matrix through liquid hydrophobization treatment and the use of coupling agent dispersion, and Melting and kneading are carried out in the extruder to achieve the orientation of the fibers.
It significantly improves the orientation effect of micro-nanofibers, enhances the mechanical properties and dimensional stability of composite materials, reduces the preparation cost, is suitable for large-scale production, and is environmentally friendly.
Smart Images

Figure CN119119609A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for directional preparation of multi-scale micro-nano fiber modified polymer granules, belonging to the technical field of composite materials. Background Art
[0002] The consumption of fossil resources is increasing day by day, and traditional petroleum-based materials are non-renewable and lack biodegradability. The problems of resource scarcity and environmental pollution are becoming increasingly serious. Biomass fiber is a natural polymer material with the advantages of abundant resources, excellent biocompatibility and good regeneration. It can degrade itself in the natural environment without polluting the environment. The biomass fiber is decomposed into micro-nano levels, and the obtained micro-nano fiber (MNF) has the characteristics of low density, high crystallinity, high surface area and high mechanical properties, and has adjustable surface chemical properties. These characteristics make MNF a good reinforcement material for polymers. MNF modified polymer composites not only have enhanced performance, but also have important significance for environmental protection, and can also reduce the cost of materials.
[0003] In recent years, research on using MNF to enhance polymers has been ongoing, but the following problems still exist:
[0004] ①MNF is unevenly dispersed in the polymer matrix and is easy to agglomerate. This will reduce the contact area between MNF and the polymer, greatly increasing the difficulty of combining with the polymer. ②The interface between the fiber and the polymer is not firmly bonded; since the surface groups of MNF show obvious hydrophilicity, while the polymer is generally hydrophobic; once the fiber and the polymer are composited, the composite effect will not be strong due to insufficient interface bonding. Currently, chemical modification or coupling agent is mainly used for treatment. Commonly used solid coupling agents, such as maleic anhydride grafted polyethylene particles, cannot be evenly wrapped on the fiber when added in small amounts, affecting the coupling effect. ③The composite material has poor strength, toughness, and dimensional stability.
[0005] There are usually two ways to prepare MNF reinforced composites: (1) Solution casting, which is to dissolve the polymer in an organic solvent or other way and then compound it with MNF; the composite material obtained by this method has good uniformity, but it is not suitable for mass production. The organic solvent used is expensive and pollutes the environment. (2) Mixing molding, which is to blend MNF and plastic into a melt and process it into a shape through mechanical methods such as extrusion, injection molding, and compression molding. This method is suitable for mass production and is green and environmentally friendly. Solving the agglomeration problem in the mixing and molding process of MNF composites, improving the orientation of MNF, and improving the strength and dimensional stability of composites are of great significance to the application of MNF modified polymer composites in a wider range of fields. Summary of the invention
[0006] Purpose of the invention: The purpose of the present invention is to provide a method for the directional preparation of multi-scale micro-nano fiber modified polymer pellets, which improves the orientation of micro-nano fibers during the melt mixing process of the extruder, and the prepared modified polymer pellets have high strength and stable size.
[0007] Technical solution: The present invention provides a method for directional preparation of multi-scale micro-nano fiber modified polymer granules, comprising the following steps:
[0008] (1) crushing softwood pulp into micron fibers with a diameter of 50-150 μm, and subjecting the micron fibers to sufficient swelling treatment; placing a portion of the swollen micron fibers in a high-speed mixer to defibrate into micron fibers with a diameter of 10-100 μm;
[0009] (2) placing the micron fibers after high-speed stirring in step (1) in an ultrafine grinder to further defiberize into micro-nano fibers with a diameter of 100 nm-10 μm;
[0010] (3) mixing the micron fiber with a diameter of 10-100 μm obtained in step (1) and the micro-nano fiber with a diameter of 100 nm-10 μm obtained in step (2) in proportion to obtain multi-scale micro-nano fibers;
[0011] (4) soaking the multi-scale micro-nano fibers in a hydrophobic modifier and vacuum filtering; then adding the multi-scale micro-nano fibers into a coupling agent dispersion and stirring evenly, vacuum filtering and drying again to obtain modified multi-scale micro-nano fibers;
[0012] (5) mixing the modified multi-scale micro-nano fibers, plastic powder, and additives, and stirring at high speed to uniformly obtain a mixture;
[0013] (6) The mixed material is melt-granulated.
[0014] The preparation method of the present invention aims at the problems of uneven fiber dispersion and agglomeration in the production process of micro-nano fiber / polymer composite materials. The micro-nano fibers are modified by the method of "liquid hydrophobic-coupling double-coated micro-nano fibers", and then melt-mixed with plastics in an extruder to improve the orientation effect of the micro-nano fibers. Specifically, the method includes:
[0015] 1. Liquid hydrophobic treatment
[0016] After being treated with a liquid hydrophobic modifier, the surface properties of the micro-nano fibers change and become hydrophobic, reducing the interfacial tension with the plastic matrix. This can: ① Improve compatibility: Liquid hydrophobic modification can form a uniform protective film on the surface of MNF. The hydrophobicized micro-nano fibers (MNF) have better compatibility with the hydrophobic plastic matrix, which helps the fibers to be evenly distributed and oriented in the plastic matrix. ② Reduce hygroscopicity: The hydrophobic treatment reduces the hygroscopicity of MNF, avoids expansion and curling during mixing, and helps the fibers to maintain orientation.
[0017] 2. Coupling agent treatment
[0018] The coupling agent dispersion can be evenly mixed with MNF, so that the coupling agent is effectively distributed in all parts of MNF, and the compatibility of MNF and plastic matrix is enhanced. This helps: ① Enhance the interfacial bonding force: The coupling agent forms a chemical bond between MNF and plastic matrix, which enhances the interfacial bonding force between the two, making MNF more stable and easier to maintain orientation during the mixing process. ② Reduce fiber agglomeration: The coupling treatment makes the MNF more evenly dispersed in the plastic matrix, reduces the agglomeration phenomenon between MNF, and thus helps the fiber to be oriented.
[0019] 3. Extruder mixing
[0020] During melt mixing in the extruder, the rotation and shearing action of the screw can help the MNF to be oriented in the plastic matrix. The MNF treated with hydrophobic coupling has a stronger interface with the plastic matrix and is more evenly dispersed, which reduces the disorder and agglomeration of the fibers during mixing, thereby improving the orientation effect.
[0021] The liquid hydrophobic agent soaking and coupling agent dispersion liquid mixing adopted in the present invention can ensure the effective distribution of the hydrophobic agent and the coupling agent in various parts of the MNF, so that the hydrophobic-coupling double coating is formed on the surface of the MNF. When compounded with the plastic, the MNF can achieve better orientation in the flow process of melt blending extrusion to form an intercalated structure.
[0022] In the method, the fiber is mechanically defibrated into MNF, which has a good fibrillation effect and is easy to achieve good physical interface bonding when compounded with plastic, that is, mechanical rivet bonding; the prepared fiber is a multi-scale micro-nano fiber with a certain aspect ratio.
[0023] Furthermore, the swelling treatment in step (1) includes a primary swelling treatment using a NaOH solution and a secondary swelling treatment using hydrochloric acid.
[0024] Furthermore, the specific steps of the swelling treatment are to place the micron fiber in a 3-5% NaOH solution, treat it in a 95°C water bath for 2 hours, then place it at room temperature for 12 hours, and wash it with distilled water or deionized water until it is neutral; then treat it with 1% hydrochloric acid in an 80°C water bath for 2-4 hours, and wash it with distilled water or deionized water until it is neutral.
[0025] Furthermore, the mass ratio of the micron fibers to the micro-nano fibers in step (3) is 7:3.
[0026] Furthermore, the hydrophobic modifier described in step (4) includes γ-aminopropyltriethoxysilane or alkenyl succinic anhydride.
[0027] Furthermore, the coupling agent described in step (4) includes maleic anhydride grafted polyethylene powder or maleic anhydride grafted polypropylene powder.
[0028] Furthermore, the mass ratio of the modified multi-scale micro-nano fibers, plastic powder and additives in step (5) is 10-50%: 46-88%: 2-4%.
[0029] Furthermore, during the melt granulation in step (6), the extruder temperature is set to 158-165° C. and the screw speed is set to 20-30 rpm.
[0030] The present invention also provides modified polymer granules prepared according to the method.
[0031] The present invention also provides the use of the modified polymer granules in the preparation of automobile parts, electronic product parts and building substrates.
[0032] Beneficial effects: Compared with the prior art, the present invention has the following outstanding and significant advantages: The present invention adopts the method of "liquid hydrophobic-coupled double-coated micro-nano fiber" to modify the micro-nano fiber, which not only improves the compatibility of the micro-nano fiber with the plastic matrix, but also enhances the stability and dispersibility of the fiber, so that the agglomeration of the microfiber is significantly reduced. Combined with the screw mixing action of the extruder, the fiber can be more easily oriented along the flow direction, thereby improving the mechanical properties and other physical properties of the composite material. The preparation method of the present invention has a simple process and low preparation cost, and can effectively reduce the consumption of fossil resources; the composite material obtained has excellent performance, high strength and dimensional stability, and can be widely used in the fields of automobile manufacturing, electronic products, building substrates, etc., and has industrial value. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 Transmission electron microscopy images of the morphology of broomed micro-nanofibers (MNF), (a) magnified 1000 times, (b) magnified 5000 times;
[0034] Figure 2This is the cross-sectional scanning electron micrograph of the polyethylene of the control group;
[0035] Figure 3 The cross-sectional scanning electron micrographs of MNF-modified polyethylene, (a) magnified 250 times, (b) magnified 800 times;
[0036] Figure 4 The flexural mechanical properties of MNF modified polymer pellets are as follows: (a) flexural strength, (b) flexural modulus;
[0037] Figure 5 This is the linear thermal expansion coefficient of MNF modified polymer pellets. DETAILED DESCRIPTION
[0038] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0039] Example 1
[0040] (1) Take a softwood pulp board of appropriate weight and cut it into pieces with a size of about 0.5 x 0.5 cm. 2 The softwood pulp board is broken into micron fibers using a common turbine mill, with a diameter distribution of 50-150μm and a length of about 1-3mm. The micron fibers are subjected to swelling treatment: placed in a 5% sodium hydroxide solution, treated in a 95℃ water bath for 2h, the fibers after the water bath are placed at room temperature for 12h, and then washed with deionized water until neutral; then treated in a 1% hydrochloric acid water bath at 80℃ for 3h to continue to fully swell the fibers, and washed with deionized water until neutral after the swelling is completed.
[0041] (2) The micron fibers after swelling treatment in step (1) are placed in a high-speed mixer and stirred for 3-5 minutes at a speed of 10,000 rpm to defibrinate into fibers with a diameter of about 10-100 μm. The fibers are then placed in an ultrafine grinder and the scale is adjusted to obtain micro-nano fibers with a diameter of 100 nm-10 μm.
[0042] The fiber effect was observed by transmission electron microscopy. The micro-nano fibers ( Figure 1 ) It can be seen that after mechanical defibration, the micro-nano-level fibers (100nm-10μm) have a good fibrillation effect. The single fiber is fibrillated, and the micron fiber is accompanied by nanofibers. When the extruder is melted and mixed at high temperature, the fibrillated fiber can greatly increase the specific surface area combined with the polymer matrix, and the two are easy to form a mechanical rivet combination, which improves the mechanical properties.
[0043] (3) The micron fibers (10-100 μm) and micro-nano fibers (100 nm-10 μm) prepared in step (2) are mixed for later use, wherein the mass ratio of the micron fibers to the micro-nano fibers is 7:3, thereby obtaining multi-scale micro-nano fibers (MNF).
[0044] (4) The multi-scale MNF prepared in step (3) is placed in a liquid hydrophobic modifier (such as γ-aminopropyltriethoxysilane) for modification, that is, the MNF and γ-aminopropyltriethoxysilane are mixed and stirred at a mass ratio of 1:1 to perform hydrophobic modification to prevent the agglomeration of the defibrated micro-nano wood fibers. The hydrophobic MNF is then placed in a coupling agent dispersion, such as: maleic anhydride grafted polyethylene powder (micro-nano scale) and a solvent (such as ethyl acetate) are mixed at a ratio of 1:20 to prepare a dispersion, and then the MNF and the coupling agent dispersion are stirred at a high speed at a mass ratio of 1:2 to ensure that the coupling agent is effectively distributed in all parts of the micro-nano fibers. After uniform mixing, the hydrophobic-coupling modified MNF slurry is obtained by vacuum filtration. The MNF slurry is then dried to obtain the modified MNF for standby use.
[0045] After the liquid hydrophobic coupling, the micro-nano fiber of the present application realizes double coating on the fiber surface. The liquid hydrophobic coupling treatment enhances the compatibility of MNF with the hydrophobic plastic matrix, makes the fiber easier to disperse evenly, and reduces the agglomeration between MNF.
[0046] (5) The modified MNF, plastic powder (high-density polyethylene), and additive (polyethylene wax) were placed in a high-speed mixer in a certain proportion and dispersed evenly to obtain a mixture at a speed of 10,000 rpm. Three mixtures with different mass proportions were prepared respectively: 1. The modified MNF content was 30%, the plastic powder content was 67%, and the additive content was 3%; 2. The modified MNF content was 20%, the plastic powder content was 77%, and the additive content was 3%; 3. The modified MNF content was 10%, the plastic powder content was 90%, and no additive was required.
[0047] (6) The mixed material is placed in an extruder to extrude a specimen, the temperature of the extruder is set to 165° C., and the screw speed is set to 30 rpm, so as to obtain a micro-nano fiber modified polyethylene specimen.
[0048] The control group polyethylene ( Figure 2 ) and modified MNF content of 20% micro-nano fiber modified polyethylene were subjected to electron microscope scanning ( Figure 3 ), the results showed that the cross-section morphology of the polyethylene in the control group was relatively smooth and the layering was not strong, while the surface of the polyethylene modified by micro-nano fibers ( Figure 3 (a) Fracture morphology shows a layer-by-layer assembled and layer-by-layer intercalated structure, with micro-nano fibers oriented along the flow direction of the polymer matrix. Figure 3 (b) The fibers are evenly dispersed in the polymer matrix, and obvious wire drawing can be seen, which helps to improve its mechanical properties.
[0049] (7) The mixed material strips obtained by extrusion molding are granulated to obtain modified polymer pellets.
[0050] (8) The pellets were placed in an injection molding machine and molded into flexural bars at an injection molding temperature of 166°C. The flexural strength of the flexural bars with different fiber contents was tested using a universal mechanical testing machine ( Figure 4 The thermal expansion coefficient of the samples was measured by a static thermomechanical analyzer (TMA) at a temperature range of -30 to 60 degrees Celsius. A polyethylene (HDPE) sample was set as a control group.
[0051] The results show that the flexural strength of the flexural specimen containing mixture 1 is 42.9MPa and the flexural modulus is 2060.8MPa, which are 100% and 162% higher than those of the polyethylene sample in the control group, respectively. The linear thermal expansion coefficient is 84×10 -6 / K, which is about half of the polyethylene sample in the control group, and the thermal stability is greatly improved. The flexural strength of the flexural specimen containing mixture 2 reaches 35MPa, and the flexural modulus reaches 1600.9MPa, which are 64% and 103% higher than those of the polyethylene sample in the control group, respectively. The linear thermal expansion coefficient is 94×10 -6 / K, which was 83×10 lower than that of the control group polyethylene -6 / K. The bending strength of the flexural specimen containing mixture 3 reached 28.2MPa, and the bending modulus reached 1180.8MPa, which was 32% and 50% higher than that of the pure high-density polyethylene sample. The linear thermal expansion coefficient was 122×10 -6 / K, which was 55×10 lower than that of the control group polyethylene -6 / K. It shows that the flexural strength and modulus of the modified polymer pellets increase with the increase of the modified MNF content. The linear thermal expansion coefficient of the modified polymer pellets decreases with the increase of the modified MNF content, which means that the dimensional stability is greatly improved with the increase of the modified MNF content.
Claims
1. A method for directional preparation of multi-scale micro-nano fiber modified polymer particles, characterized in that: The following steps are involved: (1) crushing softwood pulp into micron fibers with a diameter of 50-150 μm, and subjecting the micron fibers to sufficient swelling treatment; placing the swollen micron fibers in a high-speed mixer to defibrate into micron fibers with a diameter of 10-100 μm; (2) placing the micron fibers after high-speed stirring in step (1) in an ultrafine grinder to further defiberize into micro-nano fibers with a diameter of 100 nm-10 μm; (3) mixing the micron fiber with a diameter of 10-100 μm obtained in step (1) and the micro-nano fiber with a diameter of 100 nm-10 μm obtained in step (2) in proportion to obtain multi-scale micro-nano fibers; (4) soaking the multi-scale micro-nano fibers in a hydrophobic modifier and vacuum filtering; then adding the multi-scale micro-nano fibers into a coupling agent dispersion and stirring evenly, vacuum filtering and drying again to obtain modified multi-scale micro-nano fibers; (5) mixing the modified multi-scale micro-nano fibers, plastic powder, and additives, and stirring at high speed to uniformly obtain a mixture; (6) The mixed material is melt-granulated.
2. The method according to claim 1, characterized in that: The swelling treatment in step (1) includes a primary swelling treatment using a NaOH solution and a secondary swelling treatment using hydrochloric acid.
3. The method according to claim 2, characterized in that The specific steps of the swelling treatment are to place the micron fiber in a 3-5% NaOH solution, treat it in a 95°C water bath for 2 hours, place it at room temperature for 12 hours, and wash it with distilled water or deionized water until it is neutral; then treat it with 1% hydrochloric acid in an 80°C water bath for 2-4 hours, and wash it with distilled water or deionized water until it is neutral.
4. The method according to claim 1, characterized in that: The mass ratio of the micron fibers to the micro-nano fibers described in step (3) is 7:
3.
5. The method according to claim 1, characterized in that The hydrophobic modifier described in step (4) includes γ-aminopropyltriethoxysilane or alkenylsuccinic anhydride.
6. The method according to claim 1, characterized in that The coupling agent described in step (4) includes maleic anhydride grafted polyethylene powder or maleic anhydride grafted polypropylene powder.
7. The method according to claim 1, characterized in that The mass ratio of the modified multi-scale micro-nano fibers, plastic powder and additives described in step (5) is 10-50%: 46-88%: 2-4%.
8. The method according to claim 1, characterized in that During the melt granulation in step (6), the extruder temperature is set to 158-165° C. and the screw speed is set to 20-30 rpm.
9. A modified polymer granular material prepared according to the method of any one of claims 1 to 8.
10. Use of the modified polymer granules according to claim 9 in the preparation of automobile parts, electronic product parts and building substrates.
Citation Information
Patent Citations
Method of using surfactant to disperse micro-nano cellulose to prepare polyolefin-based composite
CN109081988A
Preparation process of multi-scale fiber reinforced polymer composite powder
CN111393840A
Preparation method of micro-nano cellulose reinforced high-density polyethylene composite material
CN112759810A
Oriented nanofibers embedded in polymer matrix
EP1803763A1
